Late Quaternary colluvial deposits in the Bocaina Plateau, southeastern Brazil highlands: age and palaeoenvironmental consequences. (25th July 2012) - Hiruma, Silvio Takashi; Modenesi‐Gauttieri, May Christine; Riccomini, Claudio
<x xml:space="preserve">Abstract</x> Despite the generalized occurrence of colluvial deposits in the humid tropical areas of southeastern Brazil, regional correlation is difficult because the deposits are discontinuous, and chronological data are very scarce and scattered. For the first time, colluvial deposits in the Bocaina Plateau are described, including 18 radiocarbon ages from 12 profiles. The plateau is located on the eastern flank of the Continental Rift of Southeastern Brazil and is the highest part of the Serra do Mar, with elevations up to 2000 m above sea level. Because the Bocaina Plateau is part of the summit surfaces of southeastern Brazil, it was subjected to specific climatic conditions during the Quaternary. Colluvial deposits on the lower hillslopes and edges of amphitheatres can show complex sequences with up to three intercalated dark humic horizons, corresponding to Late Pleistocene and Holocene phases of morphodynamic activity and pedogenesis. Ages of palaeosols vary from 650±50 a BP to 36 880±980 a BP. Landforms and colluvia on the Bocaina Plateau are very similar to those found on the opposite flank of the continental rift, on the Campos do Jordão Plateau. Ages of buried soils point to similar soil formation and colluviation episodes in the two plateaus. As in Campos do Jordão, the succession of erosive, depositional and pedogenetic processes on the altos campos hillslopes is probably related to late Quaternary climate changes.